2015
DOI: 10.1016/j.jpeds.2015.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Physicians and Physician Trainees Rarely Identify or Address Overweight/Obesity in Hospitalized Children

Abstract: Objectives To determine how frequently physicians identify and address overweight/obesity in hospitalized children and to compare physician documentation across training level (medical student, intern, resident, attending). Study design We conducted a retrospective chart review. Using an administrative database, Centers for Disease Control and Prevention body mass index calculator, and random sampling technique, we identified a study population of 300 children aged 2–18 years with overweight/obesity hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
(28 reference statements)
1
14
1
Order By: Relevance
“…27,33,45 Some studies indicate error or inaccuracy in overweight and obesity coding 14 ; however, others, as in our study, demonstrate lack of provider diagnosis. 27,45 There could be many reasons for lack of diagnosis. Provider and patient sensitivity and bias have been shown to influence provider diagnosis and treatment of overweight and obesity.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…27,33,45 Some studies indicate error or inaccuracy in overweight and obesity coding 14 ; however, others, as in our study, demonstrate lack of provider diagnosis. 27,45 There could be many reasons for lack of diagnosis. Provider and patient sensitivity and bias have been shown to influence provider diagnosis and treatment of overweight and obesity.…”
Section: Discussioncontrasting
confidence: 43%
“…21 Identifying, plotting, and monitoring BMI percentile are essential steps in the algorithm 22 and are recommended for all hospitalized children by the National Association of Children' s Hospitals and Related Institutions, 23 but studies have shown that providers in both primary care and inpatient settings are failing to measure and monitor BMI percentile. [24][25][26] A recent study by King et al 27 described lack of identification and treatment of overweight and obesity in hospitalized children; however, only a small number of patients with asthma were included, and results specific to the patients with asthma were not described.…”
mentioning
confidence: 99%
“…18,19 However, it is difficult to interpret these results, specifically because the documentation and coding of obesity occurs even less frequently in the hospital than in primary care. Rates of obesity documentation or diagnosis in the hospital range from 8% to 18% in single-center studies, [20][21][22][23] with obesity more often identified in girls, children of color, and older children. 20 To better understand the factors driving inpatient provider documentation of obesity, we conducted a retrospective chart review to identify patient characteristics associated with the documentation of weight status and related obesity management recommendations.…”
mentioning
confidence: 99%
“…The risks of obesity in childhood are well documented; however, there is a paucity of evidence regarding the impact of short-term nutritional management and periods of deficit in overweight/obese children and the subsequent impact on length of stay, morbidity or mortality. A recent study in the USA found that physicians and their trainees rarely identified or addressed overweight/obesity in hospitalised children26 and this therefore needs addressing. Although STAMP and PYMS tools are designed to identify those who are undernourished, we included those who were overweight/obese into the at-risk group for analysis as these children are, although slightly different, still are at nutritional risk.…”
Section: Discussionmentioning
confidence: 99%